Effects of Pb concentration on phase, microstructure and electrical properties of Bi 3.25La 0.75Ti 3O 12 ceramics - Lawita P. (2014)
In this work, effects of Pb-doping concentration on phase, microstructure and electrical properties of bismuth lead lanthanum titanate (Bi 1-xPb x) 3.25La 0.75Ti 3O 12 or BPLT ceramics when x = 0, 0.01, 0.03, 0.05, 0.07, 0.09 and 0.1 were investigated. Phase analysis by X-ray diffraction indicated the existence of orthorhombic phase for all BPLT powders and ceramics. Microstructural investigation using scanning electron microscope showed that all ceramics composed mainly of plate-like grains. An increase in PbO doping content reduced not only diameter and thickness of the grains but also density of the ceramics. Electrical conductivity was found to decrease while dielectric constant increased with Pb-doping concentration. Small reduction of remanent polarization and coercive field was observed in Pb-doped samples. © 2012 Elsevier B.V. All rights reserved.